CONCEPTUAL FRAMEWORK FOR OPEN-ENDED LABORATORY IN GEOTECHNICAL LABORATORY COURSE - Badrul Nizam Ismail; Rozaini Ramli; Anas Ibrahim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The term "open-ended laboratory" (OEL) describes laboratory activities where each individual or group doing the activities will have a different final result. Not only does the end part vary as the openness scale rises, but so do the beginning and intermediate parts. The conceptual framework for OEL in the Geotechnical Laboratory course is provided in this article. The three levels of the laboratory work are OEL1, OEL2, and OEL3. OEL1 is simple to implement, however OEL2 and OEL3 require explanation in order to provide a summary of the differences between each level of OEL. In summary, it is critical to correctly execute OEL3 in the first year of study since it serves as the foundation for carrying out the final year project.